Investigation of high gamma‐glutamyltransferase syndrome in California Thoroughbred racehorses. (15th November 2022) - Peng, Sichong; Magdesian, K. Gary; Dowd, Joseph; Blea, Jeffrey; Carpenter, Ryan; Ho, Wayne; Finno, Carrie J.
Abstract: Background: Increases in serum gamma‐glutamyltransferase (GGT) activity have been reported in Thoroughbred (TB) racehorses and associated with maladaptation to training but the underlying etiology remains unknown. Hypothesis/Objectives: Classify the etiology of high GGT syndrome in racing TBs by assessment of pancreatic enzymes, vitamin E concentrations, and both a candidate gene and whole genome association study. We hypothesized that a genetic variant resulting in antioxidant insufficiency or pancreatic dysfunction would be responsible for high GGT syndrome in TBs. Animals: A total of 138 California racing TBs. Amylase: n = 31 affected (serum GGT activity ≥60 IU/L), n = 52 control (serum GGT activity <40 IU/L). Lipase: n = 19 affected, n = 35 control. Serum α‐tocopherol concentrations: n = 32 affected, n = 46 control. Genome‐wide association study (GWAS): 36 affected, 58 control. Whole genome sequencing: n = 5 affected, n = 5 control. Methods: Biochemical and vitamin analytes were compared among cohorts. A GWAS was performed and a subset of TBs underwent whole genome sequencing to interrogate candidate genes and positional genetic regions. Results: Serum lipase and amylase activity and α‐tocopherol concentrations did not differ between groups. No genetic variants were identified in 2 candidate genes ( UGT1A1 and GGT 1) that associated with the phenotype. Four single nucleotide polymorphisms (SNPs) approached a suggestive association with the phenotype ( P = 2.15 × 10 −5 ), defining a 100 kb region on chromosome 5 surrounding cluster of differentiation 1a ( CD1A1 ), a transmembrane gene related to the major histocompatibility complex. Conclusions and Clinical Importance: An underlying genetic etiology may exist for high GGT syndrome in racing TBs, similar to genetic disorders in humans.